Phenological stages of a Stevia rebaudiana genebank according to BBCH scale = Estadios fenológicos de un banco de germoplasma de Stevia rebaudiana de acuerdo a la escala BBCH - Budeguer, Carlos Jorge (2024)
To evaluate the phenological stages of Stevia rebaudiana growing in Tucumán, Argentina, the Biologische Bundesanstalt, Bundessortenamt and Chemical Industry (BBCH) scale was used. The method was first applied in S. rebaudiana in France in 2020. Phenological data were collected from seven genotypes of the S. rebaudiana Genebank of the Estación Experimental Agropecuaria Famaillá, INTA and the duration of each phase of development was calculated using the growing degree days (GDD) in 2021-2022 season. Stages 1 to 9 were clearly identified and acumulate 291 to 2498 GDD between November 3, 2021, and March 23, 2022. The knowledge of these phenological stages of S. rebaudiana at the local agroecological conditions will be useful for its agronomic management and breeding.